2015
DOI: 10.1007/s00382-015-2586-1
|View full text |Cite
|
Sign up to set email alerts
|

Regional Arctic sea ice variations as predictor for winter climate conditions

Abstract: suggesting changing predictive skill dependent on sign and amplitude of the anomaly. The results confirm the importance of realistic sea ice initial conditions for seasonal forecasts. However, correlations do seldom exceed 0.6 indicating that Arctic sea ice variations can only explain a part of winter climate variations in northern mid and high latitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 62 publications
9
59
0
Order By: Relevance
“…Some studies noted that reduced autumn ice extent leads to an atmospheric winter circulation that resembles the negative phase of the North Atlantic Oscillation (NAO), with cold winter temperature anomalies in Eastern Europe, e.g. Koenigk et al (2016). More recent studies however note that the observed trends are not robust when tested over longer time periods and that they seem to be at least partly caused by natural variations (Koenigk and Brodeau 2017).…”
Section: Climate Change Projectionsmentioning
confidence: 90%
“…Some studies noted that reduced autumn ice extent leads to an atmospheric winter circulation that resembles the negative phase of the North Atlantic Oscillation (NAO), with cold winter temperature anomalies in Eastern Europe, e.g. Koenigk et al (2016). More recent studies however note that the observed trends are not robust when tested over longer time periods and that they seem to be at least partly caused by natural variations (Koenigk and Brodeau 2017).…”
Section: Climate Change Projectionsmentioning
confidence: 90%
“…This cooling is related to a strong reduction in the AMOC, itself due to reduced deep water formation in the Labrador Sea. The observed trend towards a more negative phase of the North Atlantic Oscillation (NAO) and the observed linkage between autumn Arctic ice variations and NAO are et al 2009) and a number of recent studies suggested linkages between the recent sea ice loss and mid-latitude weather and climate extremes (Petoukhov and Semenov 2010;Francis et al 2009;Francis and Vavrus 2012;Yang and Christensen 2012;Overland and Wang 2010;Hopsch et al 2012;Garcia-Serrano and Frankkignoul 2014;Liptak and Strong 2014;Koenigk et al 2016). Most of these studies found that reduced autumn ice extent leads to an atmospheric winter circulation that resembles the negative phase of the North Atlantic Oscillation (NAO).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggested a possible link between the observed sea ice reduction and the large scale atmospheric circulation and mid-latitude air temperature (Jaiser et al 2013;Inoue et al 2012;Petoukhov and Semenov 2010;Hopsch et al 2012;Overland et al 2011;Peings and Magnusdottir 2014;Rinke et al 2013;Koenigk et al 2016). Most of these studies used either the difference between the last decade (with little ice) and the previous two (with much ice), or they used detrended time series to assess the atmospheric response to sea ice variability and trend.…”
Section: Arctic-mid Latitude Linkagesmentioning
confidence: 99%
“…Therefore, the comparison between our central and wide domains demonstrates the impact of domain choice, with generally better performance when using the central domain. A decomposition of the Arctic Ocean into sub-regions such as in Koenigk et al (2016) would be a possible improvement compared to the use of a single wider domain.…”
Section: Impact Of Domain Choicementioning
confidence: 99%